We graph the first equation using the slope and intercept, and the second equation using the intercepts, to find These lines appear to hit right at (-1, -1). Let's check and make sure they work. If they don't, we may need to have our negatives developed. #filmcamerajoke The first equation was *y* = 4*x* + 3. When *x* = -1 and *y* = -1, the left-hand side of this equation is -1 and the right-hand side is 4(-1) + 3 = -1. This point works in the first equation. The second equation was -3*x* -3*y* = 6. When *x* = -1 and *y* = -1 the left-hand side of this equation is (-3)(-1) – 3(-1) = 3 + 3 = 6, which is the same as the right-hand side of the equation. Since the point (-1, -1) does indeed satisfy both equations, we can safely say that (-1, -1) is a solution to the system of equations. We feel even safer saying it now that that guy with the scythe has left the room. What was he even doing here? |